Micro-LED (Light Emitting Diode) huge transfer and release material as well as preparation method and application thereof
By using materials such as triazene resin, the problems of high-temperature shift and insufficient adhesion of strong alkali in the huge transfer of Micro LEDs are solved, and efficient and stable chip transfer and cleaning are achieved, improving product reliability and transfer yield.
Patent Information
- Application Number
- CN202510679238.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-26
- Publication Date
- 2025-08-29
AI Technical Summary
In the existing Micro LED massive transfer technology, high temperature causes chip position deviation, the material has insufficient high temperature resistance, and poor adhesion in a strong alkali environment, which affects the transfer accuracy and product reliability.
Triazene resin is used as the main material, combined with auxiliary resin, coupling agent, antioxidant and leveling agent, to form a high temperature and strong alkali-resistant Micro-LED huge transfer and release material, and achieve defect-free bonding and cleaning through ultraviolet laser release.
The transfer efficiency is improved and the production cost is reduced. The chip lighting success rate reaches more than 99.99%. The material is stable under high temperature and strong alkali conditions, and there is no residual glue.
Smart Images

Figure CN120554953A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of Micro-LED technology and relates to a Micro-LED mass transfer release material and a preparation method and application thereof. Background Art
[0002] With the rapid development of display technology, Micro LED technology has become a key candidate for future display technology due to its superior display performance, such as high brightness, low power consumption, long life, and fast response time. High-density integration of Micro LEDs is key to their application in the display field, and mass transfer technology is a core step in the manufacturing process. The efficiency and precision of this step directly determine the performance and cost-effectiveness of the final product.
[0003] However, the existing Micro LED mass transfer technology faces many challenges. In the process of transferring the Micro LED chip to the laser-induced release layer and etching, high temperature may cause the chip position to shift, which not only reduces the transfer accuracy, but also affects the overall production efficiency. In addition, the existing materials are not resistant to high temperatures during the etching process, which limits their stability and application range in high temperature environments. In the process of Micro LED mass transfer, strong alkaline solvents are also required for cleaning and treatment, which places higher requirements on the material's strong alkaline resistance and adhesion in a strong alkaline environment. However, strong adhesion often affects the cleaning performance of the material. The current Micro LED manufacturing materials perform poorly in terms of strong alkaline resistance and adhesion, which directly affects the reliability and durability of the product. Summary of the Invention
[0004] To address the shortcomings of the existing technology, the present invention aims to provide a Micro-LED mass transfer release material, its preparation method, and its application, to address the technical issues of chip offset during high-temperature processes, as well as release defects caused by mass transfer's inability to withstand strong alkaline processes and insufficient adhesion. The Micro-LED mass transfer release material of the present invention exhibits high-temperature resistance, acid and alkali resistance, strong adhesion, and easy cleaning, enabling ultra-low-energy UV laser release.
[0005] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0006] On the one hand, the present invention provides a Micro-LED mass transfer release material, wherein the raw materials for preparing the Micro-LED mass transfer release material include triazene resin, auxiliary resin, coupling agent, antioxidant, leveling agent and solvent.
[0007] The Micro-LED mass transfer release material of the present invention is resistant to high temperatures and strong alkalis, and exhibits excellent adhesion, enabling secure bonding to the chip under high temperatures and acidic and alkaline conditions, achieving defect-free bonding. Furthermore, the material should enable low-energy laser release at multiple wavelengths to improve transfer efficiency, and allow for post-process cleaning without residual adhesive residue, thereby increasing chip lighting success rates and reducing production costs.
[0008] In the present invention, the triazene resin is the main resin of the material system and is the main component of the raw materials. It has obvious ultraviolet sensitivity and wide ultraviolet absorption. Under ultraviolet laser light with low laser energy density, it can effectively produce photochemical decomposition to generate volatile small molecule fragments, achieving clean ablation without polluting the system, facilitating the cleaning and recycling of the substrate, and being resistant to strong alkali, playing an excellent role in laser-induced release of micro-light-emitting diode chips. The triazene resin is prepared by adding a monofunctional secondary amine modifier during the polymerization reaction using an aromatic primary amine diazonium salt and a secondary diamine as monomers (specifically referring to CN117089067A, the number average molecular weight of the triazene resin is below 100,000, preferably 60,000-85,000).
[0009] Preferably, based on 100% by total weight of the raw materials for preparing the Micro-LED laser mass transfer release material, the triazene resin accounts for 10% to 40%, for example, 12%, 15%, 16%, 18%, 20%, 22%, 25%, 28%, 30%, 33%, 35%, 38%, or 40%. Preferably, the triazene resin accounts for 16% to 35%.
[0010] In the present invention, the auxiliary resin plays a role in improving the heat resistance of the material system or improving the rheological properties of the material. The auxiliary resin includes but is not limited to acrylic acid-acrylate ether copolymer, polyvinyl chloride, 1,3-phenylene phosphate tetrakis (2,6-dimethylphenyl) ester (condensation polymer), acrylonitrile-butadiene-styrene copolymer (ABS), maleic anhydride-2-ethyl ethyl ester, poly-1-butene, acrylate-butylene acrylate, SBS, styrene acrylic resin (such as: acrylate-styrene copolymer), acrylonitrile, terpolymer acrylate (such as: acrylate-acrylate-styrene copolymer, etc.), vinyl acetate, methyl methacrylate-butadiene-styrene terpolymer (MBS), butylene maleate, polystyrene, or a combination of at least two thereof.
[0011] Preferably, based on 100% of the total weight of the raw materials for preparing the Micro-LED laser mass transfer release material, the auxiliary resin accounts for 1% to 20%, for example, 1%, 2%, 3%, 5%, 8%, 10%, 12%, 15%, 18%, or 20%. Preferably, the auxiliary resin accounts for 3% to 12%.
[0012] In the present invention, the coupling agent plays a role in enhancing the adhesion of the material to the substrate. The coupling agent includes but is not limited to one or a combination of at least two of LA-120, LA-151, LA-171, LA-2331, LA-297, LA-2150, LA-2151, LA-2171, LA-550, LA-551, KH550, KH560, KH570, KH590, KH792, KH793, KH602, or KH603.
[0013] Preferably, based on the total weight of the raw materials for preparing the Micro-LED laser mass transfer release material as 100%, the proportion of the coupling agent is 0.01% to 0.5%, for example, 0.01%, 0.05%, 0.08%, 0.1%, 0.2%, 0.3%, 0.4% or 0.5%. Preferably, the proportion of the coupling agent is 0.05% to 0.2%.
[0014] In the present invention, the antioxidant is primarily used to prevent oxidation side reactions in the material under high-energy laser irradiation, which can affect the performance of the adhesive. The antioxidant includes, but is not limited to, one or a combination of at least two of Antioxidant 1010, Antioxidant 1076, Antioxidant 168, Antioxidant 405, Antioxidant DLTDP, Antioxidant 1790, Antioxidant 164, Antioxidant DNP, Antioxidant DLTP, Antioxidant TNP, Antioxidant TPP, and Antioxidant MB.
[0015] Preferably, based on 100% by total weight of the raw materials for preparing the Micro-LED laser mass transfer release material, the antioxidant accounts for 0.01% to 1.0%, for example, 0.01%, 0.03%, 0.05%, 0.08%, 0.1%, 0.15%, 0.2%, 0.3%, 0.5%, 0.8%, or 1.0%. Preferably, the antioxidant accounts for 0.05% to 0.5%.
[0016] In the present invention, the leveling agent can reduce the surface tension of the coating, ensuring smooth and glossy coating of the glue on the substrate, and improving TTV. The leveling agent includes, but is not limited to, one or a combination of at least two of acrylic leveling agents (e.g., acrylate-functional polyester-modified polydimethylsiloxane solution (xylene solvent)), fluorocarbon leveling agents (e.g., fluorocarbon-modified polyolefin wax), and silicone leveling agents (e.g., BYK 306, BYK 307, BYK 333, etc.).
[0017] Preferably, based on 100% by total weight of the raw materials for preparing the Micro-LED laser mass transfer release material, the leveling agent accounts for 0.05%-2.0%, for example, 0.05%, 0.08%, 0.1%, 0.5%, 0.8%, 1%, 1.3%, 1.5%, 1.8%, or 2.0%. Preferably, the leveling agent accounts for 0.1% to 1.0%.
[0018] In the present invention, the solvent primarily functions to dissolve and disperse the resin in the organic solvent to form a dispersion, and the addition of necessary additives facilitates the formation of a uniformly dispersed and uniformly composed system. The solvent includes, but is not limited to, one or a combination of at least two of ketones, aromatic hydrocarbons, ethers, amides, dimethyl sulfoxide, decalin, or ester solvents.
[0019] Preferably, the ketone solvent includes but is not limited to one or a combination of at least two of acetone, butanone, cyclohexanone or isophorone.
[0020] Preferably, the aromatic hydrocarbon solvent includes but is not limited to toluene and / or trimethylbenzene.
[0021] Preferably, the ether solvent includes but is not limited to one or a combination of at least two of dioxane, 1,3-dioxolane, 2,2,4,4,5,5-hexamethyl-1,3-dioxolane, 2,2-dimethoxy-4-(trifluoromethyl)-1,3-dioxolane ether, tetrahydrofuran or fluorinated hexacyclic coordination ether.
[0022] Preferably, the amide solvent includes but is not limited to dimethylformamide and / or N,N-dimethylacetamide.
[0023] Preferably, the ester solvent includes but is not limited to one or a combination of at least two of ethyl acetate, ethyl acetate, butyl acetate, isopropyl acetate, propyl acetate, isoamyl acetate, benzyl acetate, butyl butyrate, trimethyl phosphate, triethyl phosphate, ethyl acrylate, methyl methacrylate, dioctyl adipate or propylene glycol monomethyl ether acetate.
[0024] Preferably, when the solvent is a combination of at least two of the above solvents, the number of solvent types in the combination does not exceed 4.
[0025] Preferably, based on the total weight of the raw materials for preparing the Micro-LED laser mass transfer release material as 100%, the proportion of the solvent is 50% to 85%, for example, 50%, 53%, 55%, 58%, 60%, 65%, 68%, 70%, 73%, 75%, 78%, 80%, 83% or 85%.
[0026] In another aspect, the present invention provides a method for preparing the Micro-LED mass transfer release material as described above, the method comprising the following steps:
[0027] (1) mixing a triazene resin and an auxiliary resin, and adding a solvent thereto;
[0028] (2) Adding a coupling agent, an antioxidant, and a leveling agent to the mixed solution of step (1), mixing, and stirring to obtain the Micro-LED mass transfer release material.
[0029] Preferably, the mixing of the triazene resin and the auxiliary resin in step (1) is carried out under stirring, and the stirring speed is 30-80 rpm, for example, 30 rpm, 35 rpm, 40 rpm, 45 rpm, 50 rpm, 60 rpm, 70 rpm or 80 rpm.
[0030] Preferably, the adding of the solvent and mixing in step (1) are carried out under stirring, the stirring speed is 80-120 rpm (for example, 80 rpm, 85 rpm, 90 rpm, 100 rpm, 110 rpm or 120 rpm), the stirring time is 1-8 h (for example, 1 h, 3 h, 5 h or 8 h), and then the speed is adjusted to 120-180 rpm (for example, 120 rpm, 130 rpm, 140 rpm, 150 rpm, 160 rpm, 170 rpm or 180 rpm), and stirred for 1-8 h (for example, 1 h, 3 h, 5 h or 8 h).
[0031] Preferably, the stirring in step (2) is stirring at a stirring speed of 180-250 rpm (for example, 180 rpm, 200 rpm, 220 rpm, 240 rpm or 250 rpm) for 12-36 h (for example, 12 h, 16 h, 18 h, 20 h, 24 h, 28 h, 30 h, 33 h and 36 h), and then the speed is adjusted to 250-350 rpm (for example, 250 rpm, 280 rpm, 300 rpm, 330 rpm or 350 rpm), and stirring is continued for 12-36 h (for example, 12 h, 16 h, 18 h, 20 h, 24 h, 28 h, 30 h, 33 h and 36 h).
[0032] Preferably, the stirring in step (2) is followed by standing and then filtering to obtain the Micro-LED mass transfer release material.
[0033] In the present invention, the standing time is 12-36 h (e.g., 12 h, 16 h, 18 h, 20 h, 24 h, 28 h, 30 h, 33 h and 36 h).
[0034] In the present invention, the filtration is performed sequentially using 1 μm, 0.45 μm, and 0.2 μm filter elements.
[0035] On the other hand, the present invention provides a use of the above-mentioned Micro-LED mass transfer release material in mass transfer.
[0036] Compared with the prior art, the present invention has the following beneficial effects:
[0037] The Micro-LED mass transfer release material of the present invention can overcome the chip offset caused by the high temperature generated by the process during the mass transfer process. In the present invention, triazene resin is combined with auxiliary resin and other additives to have strong alkali resistance and can withstand the process using high temperature and strong alkali. After the process is completed, there is no residual glue on the chip and it can be cleaned without residual glue, achieving efficient chip transfer and successful lighting in subsequent processes. The transfer yield is as high as over 99.99%. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 This is an optical microscope photograph of a Micro-LED device after mass transfer using the Micro-LED laser mass transfer release material of Example 1. DETAILED DESCRIPTION
[0039] The technical solution of the present invention is further described below by way of specific embodiments. It should be understood by those skilled in the art that the embodiments are merely to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0040] The raw materials used in the following examples and comparative examples are as follows:
[0041] Triazene resin: a nitrogen-containing polymer prepared with reference to Example 1 in CN117089067A.
[0042] Styrene-N-phenylmaleimide-maleic anhydride graft copolymer: purchased from Shenzhen Huixin Plastic Chemical Co., Ltd., X-064;
[0043] Polycarbonate: purchased from Dongguan Sudashi Polymer Materials Co., Ltd., SDS006;
[0044] Polyimide: purchased from Shanghai Teflon New Material Technology Co., Ltd., JGN6230;
[0045] Polyetheretherketone: purchased from Shanghai Liu Zhangyang Plastics Co., Ltd., 450PF;
[0046] KH550: Sigma-Aldrich (Shanghai) Trading Co., Ltd.
[0047] KH560: Sigma-Aldrich (Shanghai) Trading Co., Ltd.;
[0048] KH570: Sigma-Aldrich (Shanghai) Trading Co., Ltd.;
[0049] KH590: Sigma-Aldrich (Shanghai) Trading Co., Ltd.;
[0050] BYK 306: Edrison Laboratory;
[0051] BYK 307: Edrison Laboratory;
[0052] BYK 333: Edrison Laboratory;
[0053] Antioxidant 1010: Sigma-Aldrich (Shanghai) Trading Co., Ltd.
[0054] Antioxidant 1076: Sigma-Aldrich (Shanghai) Trading Co., Ltd.
[0055] Antioxidant 168: Sigma-Aldrich (Shanghai) Trading Co., Ltd.
[0056] Antioxidant 164: Sigma-Aldrich (Shanghai) Trading Co., Ltd.
[0057] Example 1
[0058] This embodiment provides a Micro-LED mass transfer release material, the raw materials for preparing which include triazene resin, auxiliary resin, coupling agent, antioxidant, leveling agent and solvent, and the weight percentage content of each component is shown in Table 2.
[0059] The preparation method of the Micro-LED mass transfer release material is as follows:
[0060] (1) Add triazene resin and auxiliary resin into a 10L stirring kettle in order according to the ratio of the formula, and stir slowly at 50 rpm;
[0061] (2) Add 70% of the solvent according to the formula to the stirred tank, adjust the stirring speed to 100 rpm, stir for 4 hours, then adjust the speed to 150 rpm, and stir for 4 hours;
[0062] (3) Add the coupling agent, antioxidant, and leveling agent to the stirring tank in sequence according to the formula, and use the remaining 30% solvent to flush the materials on the inner wall of the stirring tank into the stirring tank and mix with other materials. Adjust the speed to 200 rpm and stir for 24 hours;
[0063] (4) The speed was adjusted to 300 rpm and stirring was continued for 24 h;
[0064] (5) Let stand for 24 hours;
[0065] (6) The above glue is filtered in sequence using 1, 0.45, and 0.2 μm filter cartridges to obtain the Micro-LED mass transfer release material.
[0066] The Micro-LED mass transfer release material prepared in Example 1 is used for mass transfer. The specific method is as follows:
[0067] (1) Coating a laser-induced release layer material (i.e., the Micro-LED mass transfer release material prepared in Example 1) on a sapphire substrate to a coating thickness of 5 μm;
[0068] (2) placing the sapphire substrate coated with the laser-induced release layer material at 100° C., allowing the solvent to evaporate to form a film, thereby obtaining a sapphire substrate 1 provided with a laser-induced release layer;
[0069] (3) The sapphire substrate 2 with the LED chip and the sapphire substrate 1 with the laser-induced release layer are placed opposite each other and thermally pressed together at 60° C. for 10 minutes;
[0070] (4) using laser lift-off technology to process the sapphire substrate 2 on which the LED chip is disposed, and transferring the LED chip to the side of the laser-induced release layer away from the sapphire substrate 1;
[0071] (5) removing and cleaning the sapphire substrate 2 to obtain a sapphire substrate 1 provided with a laser-induced release layer, wherein an LED chip is provided on a side of the laser-induced release layer away from the sapphire substrate 1;
[0072] (6) Spin-coating the receiving material (TAP 7510, purchased from Shenzhen Huaxun Semiconductor Materials Co., Ltd.) onto the sapphire substrate 3 at a spin-coating speed of 800 rpm, a coating time of 60 s, and a thickness of 50 μm;
[0073] (7) curing the sapphire substrate 3 with the receiving material spin-coated thereon at 180° C. for 12 minutes to obtain a sapphire substrate 3 provided with a temporary receiving layer;
[0074] (8) placing the sapphire substrate 1 provided with a laser-induced release layer obtained in step (5) (the LED chip is provided on the side of the laser-induced release layer away from the sapphire substrate 1) and the sapphire substrate 3 provided with a temporary receiving layer obtained in step (7) in a mass transfer device, so that the LED chip and the temporary receiving layer are arranged opposite to each other and are not connected;
[0075] The distance between the surface of the laser-induced release layer away from the sapphire substrate 1 and the surface of the temporary receiving layer away from the sapphire substrate 3 is 110 μm;
[0076] The energy density used is 100mJ / cm 2 The multi-band laser irradiates the laser-induced release layer (the transfer parameters are shown in Table 1) to release the LED chips at the corresponding positions to the temporary receiving layer of the sapphire substrate 3, completing the Micro-LED laser mass transfer;
[0077] (9) Use a 1064nm laser to transfer the LED chip on the surface of the temporary receiving layer to the TFT substrate for laser mass welding.
[0078] The transfer parameters are shown in Table 1.
[0079] Table 1
[0080]
[0081] Testing or evaluating performance after mass transfer:
[0082] (1) Glass transition temperature:
[0083] The Micro-LED laser mass transfer release materials provided in the above examples and comparative examples were spin-coated on a crystallized glass sheet, dried, and scraped. The resulting film material was then subjected to DSC testing. The spin-coating conditions were 2000 rpm for 30 seconds and the drying conditions were 120°C for 10 minutes.
[0084] The glass transition temperature was tested according to the national standard GB / T 15022.2-5, wherein the experimental conditions were set on the differential scanning calorimeter, including a heating rate of 5°C / min, a nitrogen atmosphere, and a temperature range of -20 to 250°C. (2) 100-grid grade after natron: Before the 100-grid test, the Micro-LED laser mass transfer release material provided in the above-mentioned embodiment and comparative example was first spin-coated and dried on a sapphire substrate. The spin-coating conditions can be 2000 rpm @ 30s, and the drying conditions can be 120°C @ 10min. Then, the 100-grid test was performed. The 100-grid test is a test method for evaluating the surface adhesion of a material (national standard for 100-grid test: GB / T9286-2021). The specific steps are as follows:
[0085] (1) Marking and acid soaking: Use a grid knife to mark 10×10 small grids of 1 mm×1 mm on the surface of the test sample. Each mark should be deep enough to reach the bottom layer of the paint. Then soak it in 8% HCl solution for 30 minutes.
[0086] (2) Cleaning: Use a brush to clean the debris in the test area;
[0087] (3) Tape test: Use 3M No. 600 tape or tape of equivalent strength to firmly stick to the small grid to be tested, and use an eraser to rub the tape vigorously to increase the contact area and strength between the tape and the tested area;
[0088] (4) Peeling: After 4 minutes of rest, grab one end of the tape and quickly tear it off in the vertical direction (90°). Repeat the same test twice at the same location.
[0089] (5) Result evaluation: Based on the peeling condition of the coating, the adhesion grade is assessed according to the standard. Usually, the test results are expressed in numbers and letters to indicate the quality grade of adhesion;
[0090] Among them, the result level evaluation criteria of the 100-grid test are as follows:
[0091] ISO Grade 0 / ASTM Grade 5B: The edges of the cut are completely smooth, without any peeling off the edges of the grid;
[0092] ISO Grade 1 / ASTM Grade 4B: Small flakes may be present at the intersection of the cuts, with actual damage within the cross-cut area not exceeding 5%.
[0093] ISO Grade 2 / ASTM Grade 3B: The edges and / or intersections of the cut are peeled, with an area greater than 5% but less than 15%;
[0094] ISO Grade 3 / ASTM Grade 2B: Partial or large-scale peeling along the edge of the cut, or a portion of the grid is completely peeled off. The peeled area is more than 15% but less than 35%;
[0095] ISO Grade 4 / ASTM Grade 1B: Large pieces of the cut edge are peeling off, or some squares are partially or completely peeling off, the area of which is greater than 35% but not more than 65% of the specification area;
[0096] ISO Grade 5 / ASTM Grade 0B: Exceeds the previous grade.
[0097] (III) Grade after natron:
[0098] The difference between the test sample and the acid soaked sample is as follows: (1) Marking and alkali soaking: Use a grid knife to mark 10×10 1mm×1mm small grids on the surface of the test sample. Each mark should be deep enough to reach the bottom layer of the paint. Then soak the sample in a potassium hydroxide solution with a mass concentration of 40% for 10 minutes.
[0099] Other steps and evaluation criteria are the same as above.
[0100] (3) Cleaning performance: After completing the chip transfer process (the chip transfer method refers to the chip mass transfer method provided in CN118366916A), the receiving layer with the chip is immersed in the solvent corresponding to the glue solution at room temperature for 10 minutes. The receiving layer material is removed, rinsed with IPA (isopropyl alcohol), dried at 100℃ for 10 minutes, and observed under a microscope to see if there is any residual glue on the chip.
[0101] (4) Chip transfer yield: The ratio of chips that can be lit after transfer to the total transferred chips. The chip transfer method refers to the chip mass transfer method provided in CN118366916A. The Micro-LED laser mass transfer release materials provided in the above embodiments and comparative examples are used to prepare the laser-induced release layer.
[0102] The test results are shown in Table 2.
[0103] Examples 2-5 and Comparative Examples 1-5
[0104] The only difference from Example 1 is that the raw material composition is shown in Table 2.
[0105] Table 2
[0106]
[0107]
[0108] As can be seen from the table above, the Micro-LED laser mass transfer release material of the present invention has a relatively high glass transition temperature (88-112.3°C), and its 100-grid grade after natron treatment can reach 5B. When used for mass transfer, it leaves no residual adhesive on the chips, and the chip transfer yield is as high as over 99.99%.
[0109] Figure 1 This is an optical microscope (KEYENCE, VHX-X1) photograph of a Micro-LED device after mass transfer using the Micro-LED laser mass transfer release material of Example 1. As can be seen from the image, the transferred chip has no flipping, standing, or offset phenomena, and the transfer yield is high.
[0110] In Comparative Example 1, the chip transfer yield rate was significantly reduced due to the low amount of triazene resin used. In Comparative Example 2, the chip transfer yield rate was significantly reduced due to the low amount of auxiliary resin used. In Comparative Example 3, the 100-grid grade after natron treatment was reduced due to the low amount of coupling agent used, and the chip transfer yield rate was significantly reduced. In Comparative Example 4, the chip transfer yield rate was significantly reduced due to the low amount of leveling agent used. In Comparative Example 5, the chip transfer yield rate was reduced due to the low amount of antioxidant used, and the yield rate of more than 99.99% could not be achieved.
[0111] The applicant declares that the present invention uses the above-described embodiments to illustrate the Micro-LED mass transfer release material, its preparation method, and its application. However, the present invention is not limited to the above-described embodiments, which does not necessarily mean that the present invention must rely on the above-described embodiments for implementation. Those skilled in the art should understand that any improvements to the present invention, equivalent substitutions for the raw materials used, additions of auxiliary components, and selection of specific methods, etc., fall within the scope of protection and disclosure of the present invention.
Claims
1. A Micro-LED mass transfer release material, characterized in that: The raw materials for preparing the Micro-LED mass transfer release material include triazene resin, auxiliary resin, coupling agent, antioxidant, leveling agent and solvent.
2. The Micro-LED mass transfer release material according to claim 1, characterized in that: Based on the total weight of the raw materials for preparing the Micro-LED laser mass transfer release material being 100%, the proportion of the triazene resin is 10% to 40%, preferably 16% to 35%.
3. The Micro-LED mass transfer release material according to claim 1 or 2, characterized in that: The auxiliary resin includes one or a combination of at least two of acrylic acid-acrylate ether copolymer, polyvinyl chloride, 1,3-phenylene tetrakis(2,6-dimethylphenyl)phosphate, acrylonitrile-butadiene-styrene copolymer, maleic anhydride-2-2 ethyl ethyl ester, poly-1-butene, acrylate-butylene acrylate, SBS, styrene acrylic resin, acrylonitrile, terpolymer acrylate, vinyl acetate, methyl methacrylate-butadiene-styrene terpolymer, butylene maleate, and polystyrene; Preferably, based on the total weight of the raw materials for preparing the Micro-LED laser mass transfer release material being 100%, the proportion of the auxiliary resin is 1% to 20%, preferably 3% to 12%.
4. The Micro-LED mass transfer release material according to any one of claims 1 to 3, characterized in that: The coupling agent includes one or a combination of at least two of LA-120, LA-151, LA-171, LA-2331, LA-297, LA-2150, LA-2151, LA-2171, LA-550, LA-551, KH550, KH560, KH570, KH590, KH792, KH793, KH602 or KH603; Preferably, based on the total weight of the raw materials for preparing the Micro-LED laser mass transfer release material being 100%, the proportion of the coupling agent is 0.01% to 0.5%, preferably 0.05% to 0.2%.
5. The Micro-LED mass transfer release material according to any one of claims 1 to 4, characterized in that: The antioxidant includes one or a combination of at least two of antioxidant 1010, antioxidant 1076, antioxidant 168, antioxidant 405, antioxidant DLTDP, antioxidant 1790, antioxidant 164, antioxidant DNP, antioxidant DLTP, antioxidant TNP, antioxidant TPP, and antioxidant MB; Preferably, based on the total weight of the raw materials for preparing the Micro-LED laser mass transfer release material being 100%, the proportion of the antioxidant is 0.01% to 1.0%, preferably 0.05% to 0.5%.
6. The Micro-LED mass transfer release material according to any one of claims 1 to 5, characterized in that: The leveling agent includes one or a combination of at least two of an acrylic leveling agent, a fluorocarbon leveling agent, and an organic silicon leveling agent; Preferably, based on the total weight of the raw materials for preparing the Micro-LED laser mass transfer release material being 100%, the proportion of the leveling agent is 0.05%-2.0%, preferably 0.1% to 1.0%.
7. The Micro-LED mass transfer release material according to any one of claims 1 to 6, characterized in that: The solvent includes one or a combination of at least two of ketones, aromatic hydrocarbons, ethers, amides, dimethyl sulfoxide, decahydronaphthalene or ester solvents; Preferably, the ketone solvent comprises one or a combination of at least two of acetone, butanone, cyclohexanone or isophorone; Preferably, the aromatic hydrocarbon solvent includes toluene and / or trimethylbenzene; Preferably, the ether solvent comprises one or a combination of at least two of dioxane, 1,3-dioxolane, 2,2,4,4,5,5-hexamethyl-1,3-dioxolane, 2,2-dimethoxy-4-(trifluoromethyl)-1,3-dioxolane ether, tetrahydrofuran or a fluorinated hexacyclic coordination ether; Preferably, the amide solvent includes dimethylformamide and / or N,N-dimethylacetamide; Preferably, the ester solvent comprises one or a combination of at least two of ethyl acetate, ethyl acetate, butyl acetate, isopropyl acetate, propyl acetate, isoamyl acetate, benzyl acetate, butyl butyrate, trimethyl phosphate, triethyl phosphate, ethyl acrylate, methyl methacrylate, dioctyl adipate or propylene glycol monomethyl ether acetate; Preferably, when the solvent is a combination of at least two of the solvents, the number of solvent types in the combination is no more than 4; Preferably, based on the total weight of the raw materials for preparing the Micro-LED laser mass transfer release material being 100%, the proportion of the solvent is 50% to 85%.
8. The method for preparing a Micro-LED mass transfer release material according to any one of claims 1 to 7, wherein: The preparation method comprises the following steps: (1) mixing a triazene resin and an auxiliary resin, and adding a solvent thereto; (2) Adding a coupling agent, an antioxidant, and a leveling agent to the mixed solution of step (1), mixing, and stirring to obtain the Micro-LED mass transfer release material.
9. The preparation method according to claim 8, characterized in that In step (1), the triazene resin and the auxiliary resin are mixed under stirring at a stirring speed of 30-80 rpm; Preferably, the adding of the solvent and mixing in step (1) are carried out under stirring, the stirring speed is 80-120 rpm, the stirring time is 1-8 h, and then the speed is adjusted to 120-180 rpm and stirred for 1-8 h; Preferably, the stirring in step (2) is stirring at a stirring speed of 180-250 rpm for 12-36 hours, and then adjusting the speed to 250-350 rpm and continuing stirring for 12-36 hours; Preferably, the stirring in step (2) is followed by standing and then filtering to obtain the Micro-LED mass transfer release material; Preferably, the standing time is 12-36 hours; Preferably, the filtration is performed sequentially using 1 μm, 0.45 μm, and 0.2 μm filter elements.
10. Use of the Micro-LED mass transfer release material according to any one of claims 1 to 7 in mass transfer.
Citation Information
Patent Citations
Nitrogen-containing polymer capable of realizing low-energy ultraviolet cleaning ablation as well as preparation method and application of nitrogen-containing polymer
CN117089067A